Design Procedure for Optimal Multiâinput Control System via Time-domain Technique - R.J. Widodo (Institute for Research and Community Services (LPPM) ITB, 1982)
Abstract. Design procedures for Linear-optimal control systems with respect to a quadratic performance index are developed. Via a Time-domain Technique and based on the phase-variable canonical-system description, the optimal feedback vector k and the weighting matrix Q can be directly determined from the characteristic equations of the open and closed loop systems. Formerly the design procedures has been developed for single input systems, and then to be extended to multi-systems. PROSEDUR RANCANGAN UNTUK SISTEM-SISTEM KONTROL OPTIMAL DENGAN MASUKAN BANYAK MELALUI BIDANG WAKTUSari. Suatu prosedur rancangan untuk Sistem-sistem Kontrol Optimal Linier dengan indeks performans kwadrat telah dikembangkan. Berdasarkan deskripsi sistem perubah pada dan melalui bidang waktu, vector catubalik optimal k dan matrik pembobotan Q dapat ditentukan secara langsung dari persamaan-persamaan karakteristik sistem putaran terbuka dan putaran terutup. Semula prosedur rancangan dikembangkan untuk sistem-sistem masukan tunggal dan kemudian dilanjutkan untuk sistem-sistem masukan banyak.Mungkin nanti bila ybs sudah mengirimkan surat resmi saya kabari lagi Bapak. Saya sudah sampaikan hal ini ke Pa Ilik juga.